Genetic Insight Into the Insect Resistance in Bread Wheat Exploiting the Untapped Natural Diversity - Arif, Mian Abdur Rehman; Waheed, Muhammad Qandeel; Lohwasser, Ulrike; Shokat, Sajid; Alqudah, Ahmad M.; Volkmar, Christa; Börner, Andreas (Frontiers in Genetics, 2022)
Climate change is an undeniable threat to sustainable wheat production in the future as an increased temperature will significantly increase grain loss due to the increased number of generations per season of multivoltine species which are detrimental to plants. Hence, climate change will likely threaten sustainable wheat production in the future. Likewise, wheat production is under constant threat of unexpected abiotic and biotic stresses due to abrupt environmental changes or the movement of pathogens. Among insects, orange wheat blossom midge (OWBM), yellow wheat blossom midge (YWBM), saddle gall midge (SGM), thrips and frit fly (FF) are important wheat pests in the European environments which can be managed by the development of resistant cultivars. This involves the identification, confirmation, and incorporation of insect resistance sources into new high-yielding cultivars. In this investigation, we aimed to get an insight into the genetic architecture of OWBM, YWBM, SGM, thrips and FF in two different sets of wheat (winter wheat (WW) and spring wheat (SW)) panels using the tools of association mapping. The primary aim was to assess the natural phenotypic variation against naturally existing populations of the above-mentioned insects in various parts of central Germany. Another objective is to associate molecular markers with the differential phenotypic response to map loci underlying the resistance to these pests. All in all, a total of 645 and 123 significant associations were detected in WW and SW, respectively, which were confined to 246 QTLs. Many candidate genes were identified using the BLAST analysis of the sequences of associated SNPs. Some of them are involved in controlling the physical structures of plants such as stomatal immunity and closure, cuticular wax in leaf blade whereas others are involved in the production of certain enzymes in response to biotic and abiotic stresses. To our knowledge, this is the first detailed investigation that deals with YWBM, SGM, thrips and FF resistance genetics using the natural variation in wheat. The reported germplasm is also readily available to breeders across the world who can make rational decisions to breed for the pest resilience of their interest by including the resistant genotypes being reported.